Species Composition and Structure of Secondary Forest at Nunuka, North Bolaang Mongondow - Nurlita Indah Wahyuni; Yermias Kafiar (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2017)
Secondary forest of Indonesia covered about 24.2 % of total land area and dominated by post logging forest. The discourse to manage all forest area into Forest Management Unit (FMU) as the smallest management unit has been established, including post logging secondary forest. Therefore, understanding the diversity of secondary forest vegetation will help to decide its future management. This research aims to analyze composition, diversity and structure of post logging secondary forest at Nunuka, North Bolaang Mongondow of North Sulawesi. In order to accomplish the proposed objectives 30 plots of 20 m x 20 m were established in research area where number and name of tree species were identified and counted. The research was conducted on November 2014. The result recorded 84 tree species in research area. Anthocephalus macrophyllus dominated tree phase, whereas Eugenia sp. dominated both of poles and sapling. Shannon-Wiener index indicated low and medium diversity, whereas species abundance of tree, ploes and sapling were almost spread evenly. Vegetation density over all vegetation phases was 485.83 tree/ha, the average basal area of the forest was 35.15 m2/ha and the size class distribution did not resembled a reserved J-shaped pattern as found in primary forest. However J-shaped pattern showed in graphs of ten dominant species in both of tree and sapling level. Keywords: species composition, structure, secondary forest, North Bolaang Mongondow